Geneza unui clişeu: „călinescianismul” - Andrei Terian (Revista de Istorie și Teorie Literară)
In 1965, immediately after the death of Călinescu (and Gheorghe Gh. Dej also), the literary critics began to use his legacy. In “Contemporanul” Revue, Adrian Marino noticed that the Master wanted his disciples to follow his spirit, not his style. The dialog between Cornel Regman and Toma Pavel published in the “Literary Gazette” was explosive by putting in debate of “calinescianism”, considered as a dogma. Adrian Marino, in the article “Around the actual critics” defied them to be authors of some fundamental works, possibly masterpieces. In the article, Marino is also giving a definition of the “calinescianism”. For “anti-calinescians” (I. Negoitescu, Nicolae Balota, Ovidiu Cotrus), the polemics in 1966-67 mark a real insurrection. Eventually, both sides agreed that, in essence, the “calinescianism” was based on the respect for aesthetical value and the reject of the dogmatism. In the next years the debate moved to other problems, like the parallel between Călinescu and Lovinescu.